Conceptual framework for research design: practical essential points for developing a proposal in forestry sector in Nepal - Koirala, Pashupati Nath (The Initiation, 2014)
DOI: http://dx.doi.org/10.3126/init.v5i0.10265 The Initiation 2013 Vol.5; 147-152